2008
DOI: 10.1590/s1806-83242008000200006
|View full text |Cite
|
Sign up to set email alerts
|

In vitro integrity of implant external hexagon after application of surgical placement torque simulating implant locking

Abstract: The aim of this study was to evaluate the integrity of the external hexagon of an implant system with internal and external hexagons but with prosthetic connection through the external hexagon (Internal Torque, IT) in comparison with that of an implant system with external hexagon with mount (External Hexagon, EH). A device was made to measure the rotational freedom angles between implant and abutment hexagons in 10 implants from each group after the application of surgical placement torques of 45, 60 and 80 N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 11 publications
0
22
0
8
Order By: Relevance
“…In this study, the implants were inserted in self-curing acrylic resin rigid plates in pattern way using liners. It enables a specimen evaluation with appropriately fixed on the acrylic in order to decease external variables that could interfere on the results, as bone type and quality, implant thread macro and micro geometry and eve implant surface treatment [25][26][27][28][29][30] . .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the implants were inserted in self-curing acrylic resin rigid plates in pattern way using liners. It enables a specimen evaluation with appropriately fixed on the acrylic in order to decease external variables that could interfere on the results, as bone type and quality, implant thread macro and micro geometry and eve implant surface treatment [25][26][27][28][29][30] . .…”
Section: Discussionmentioning
confidence: 99%
“…Deformations in the geometry of EH caused by external torque (16) have led to the use of internal torque, since the internal area of the implant exhibits greater resistance as compared to the external area. Therefore, in order to identify possible changes in the internal area of the implant and to exclude interfering variables, the static positioning of the implants into the acrylic model was chosen for the application of torque in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the level of changes observed in the EA of both N80 and S40, 0.59% (0.038 mm 2 ) and 0.49% (0.032 mm 2 ) respectively, may affect the correct fit of the prosthesis to the implant. Studies indicate a direct correlation between implant-abutment rotational misfit and screw loosening (10,(16)(17)(18)(19).…”
Section: Hexagon Deformation Subjected To Torquementioning
confidence: 99%
“…Afterwards, the external hexagon was also shown to work as an antirotational mechanism and to orient the abutment in single tooth prostheses (Davi et al, 2008). The biomechanical complications reported are loosening or fracturing of the abutment and prostheses screws (Merz et al, 2000).…”
Section: External Hexagonmentioning
confidence: 99%
“…However, the weak-link to the fixture of the external hexagon configuration, is often referred as a fail-self mechanism for over-loading situations (Maeda et al, 2006). Davi et al (2008) evaluated the integrity of the external hexagon of an implant system with internal and external hexagons but with prosthetic connection through the external hexagon (internal torque) in comparison with that of an implant system with external hexagon with mount (external hexagon). They concluded that the internal torque implant system may be preferable in clinical situations where implant placement within a certain bone density could generate torques higher than 60 N.cm.…”
Section: External Hexagonmentioning
confidence: 99%